English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

y = ((sqrt of x) - 2) (3(sqrt of x) + 8) at P (4, 0)

Find the equation of the tangent.
I got 3x-16y-12=0 but this is wrong according to book. if possible show me the steps thannks

2007-03-17 08:50:39 · 1 answers · asked by 8 3 in Computers & Internet Software

1 answers

Try this: 3x + 8(sqrt of X) - 6(sqrt of x) -16 =
3x + 2(sqrt of x) - 16 =
12 + 4 - 16 = 0

So when x=4, y=0

It all breaks down to x = y+4

2007-03-17 08:58:56 · answer #1 · answered by jasonheavilin 3 · 0 0

fedest.com, questions and answers